2021
DOI: 10.5937/industrija49-31692
|View full text |Cite
|
Sign up to set email alerts
|

Green advertising and its impact on environmentally friendly consumption choices: A review

Abstract: Research on various environmental topics, among which is the topic of green advertising, has been growing during last three decades, but it is yet to gain its full potential. Since the topic of green advertising has been gaining rising attention of scholars, the body of knowledge on this topic has been growing as well. Green advertising in general aims to promote products produced in an environmentally-friendly manner, or to promote advertiser's corporate responsibility toward an environment. The evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…It appears that consumers' trust in the green advertisement is much affected by the extent to which green advertising claims, specifically, environmental claims that are perceived to be informative and valuable. The strength of advertising claims; clear and specific environmental claims appear to be the most relevant factor of advertising effectiveness (Krstić et al, 2021;Rooijmans, 2018;Ulusoy & Barretta, 2016). Some researchers found that vague environmental claims are perceived as greenwashing and deteriorate consumers' attitudes toward advertisements and brands (Majláth, 2017;Parguel et al, 2015;Schmuck et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It appears that consumers' trust in the green advertisement is much affected by the extent to which green advertising claims, specifically, environmental claims that are perceived to be informative and valuable. The strength of advertising claims; clear and specific environmental claims appear to be the most relevant factor of advertising effectiveness (Krstić et al, 2021;Rooijmans, 2018;Ulusoy & Barretta, 2016). Some researchers found that vague environmental claims are perceived as greenwashing and deteriorate consumers' attitudes toward advertisements and brands (Majláth, 2017;Parguel et al, 2015;Schmuck et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The terms such as sustainability, recycling, and environmentally friendly have become common appeals in green marketing targeted at households and industries. Most companies use green advertising to promote green products or services by conveying the relationship between the product and the environment and enhancing the corporate image of environmental responsibility (Krstić et al, 2021;Liao et al, 2020;Tee et al, 2014). Kumar (2017) claimed that green advertising aims to inform consumers about a company's environmental practices, build trust in environmental promises, and engage with customers.…”
Section: Trust In Green Advertisementmentioning
confidence: 99%
See 3 more Smart Citations